IMPLEMENTASI AJARAN SAD GUNA DALAM UPACARA MUNGGAH TRUNA-TRUNI LAN MEPANDES BERSAMA DI INSTITUT AGAMA HINDU NEGERI GDE PUDJA MATARAM - Wiasti, Ni Komang; Wirata, I Wayan; Sudarsini, Nengah; Saridewi, Desak Putu; Widaswara, Rieka Yulita; Prastiwi, Wida Samining (Bawi Ayah: Jurnal Pendidikan Agama dan Budaya Hindu, 2026)
The munggah truna, truni lan mepandes ceremony is part of manusa yadnya in Hinduism that signifies the process of individual maturation. In modern society, this ritual functions not only as a religious practice but also as a medium for ethical and character development. This article aims to examine the implementation of Sad Guna teachings in the collective performance of the Munggah Truna, Truni lan Mepandes ceremony at the Institut Agama Hindu Negeri Gde Pudja Mataram. This study employs a descriptive qualitative approach using observation and documentation techniques. Data were analyzed descriptively and analytically through the lens of behavior theory. The findings indicate that the collective ceremony serves as a means of habituating ethical behavior through ritual stimuli, participants’ responses, and social-religious reinforcement. Sad Guna values are internalized in the form of discipline, self-control, adherence to ritual procedures, and social responsibility. Furthermore, the ceremony demonstrates the role of a religious higher education institution in value education, community service, and the preservation of Hindu traditions and cultural identity.